Money in the computer age - Thomson, F. P. (Oxford, New York, Pergamon Press, 1968)
This book provide a record of the evolution of money and the influences brought to bear on its shape and handling methods by technologically inspired pressures.
includes index
Bibliography: p. 231-235.
usc 16/6/17
Loans
Keywords: Money; Banks and banking; Banks and banking--Data processing; Clearinghouses (Banking); International clearing